Pengukuran kemampuan literasi digital siswa sekolah dasar (Master of Elementary Education, University of Riau, 2022)
The purpose of this study was to determine and describe the digital literacy skills of elementary school students. The research was conducted using descriptive quantitative methods. The validity and reliability of the instrument were analyzed using the Rasch Model. Collecting data using interviews with 3 teachers and instruments filled in by fifth grade elementary school students. The data analysis technique is in the form of data from the measurement of students' digital literacy abilities. Data obtained from the results of student analysis of instruments that are already valid and reliable. The results showed that the research instrument used to measure students' digital literacy skills met the valid and reliable criteria and was very feasible with a validity percentage of 0.83%, and a percentage of student responses of 76.3%.